Pengaruh Disipin Kerja, Lingkungan Kerja Terhadap Kinerja Karyawan Dengan Kepuasan Kerja Sebagai Variabel Intervening Pada CV. Percetakan Fajar Mojokerto - Vingki Elisa Putri; Rahayu Rahayu; Kasnowo Kasnowo (Maeswara : Jurnal Riset Ilmu Manajemen dan Kewirausahaan, 2023)
This study aims to examine work discipline, work environment, influence on employee performance, and to test work discipline, work environment, influence employee performance with job satisfaction as an intervening variable. The population in this study are employees at CV. Fajar Mojokerto Printing. The sampling technique used the saturated sampling method and obtained a sample of 100 employees. Data analysis used descriptive statistics and inferential statistics using SmartPLS 3.2.9 as a testing tool. The results showed that work discipline has a positive effect on employee performance, work environment has a positive effect on employee performance, work discipline has a negative effect on employee performance with job satisfaction as an intervening variable, work environment has a positive effect on employee performance with job satisfaction as an intervening variable, job satisfaction positive effect on employee performance.